Explaining intention to reduce red and processed meat in the UK and Italy using the theory of planned behaviour, meat-eater identity, and the Transtheoretical model. (1st November 2021) - Wolstenholme, Emily; Carfora, Valentina; Catellani, Patrizia; Poortinga, Wouter; Whitmarsh, Lorraine
Abstract: This study aimed to contribute to the growing literature investigating the psychosocial factors associated with intentions to reduce red and processed meat consumption, given the significant negative impact of meat on public health and in contributing to climate change. A framework combining the Theory of Planned Behaviour with meat-eater identity and the Transtheoretical Model was used to explain intention to reduce red and processed meat consumption across participant samples in the UK and Italy, to identify the factors involved in encouraging behaviour change whilst also considering differences in culinary practices. University students in the UK (n = 320) and Italy (n = 304) completed an online survey including measures from the Theory of Planned Behaviour and the Transtheoretical Model, as well as a measure of meat-eater identity. The results showed differences in the relative impact of subjective norm, perceived behavioural control, and meat-eater identity, on behavioural intention across the different stages of change and across the two countries. On the other hand, attitude remained a stable predictor across the different stages of change and in both countries. The results are discussed in relation to existing literature, with the goal of increasing understanding of how reduced meat consumption might be encouraged across different populations.